PENGARUH KOMBINASI KOMPOS TRICHODERMA DAN MIKORIZA VESIKULAR ARBUSKULAR (MVA) TERHADAP PERTUMBUHAN TANAMAN KEDELAI (GLYCINE MAX (L.) MERILL) PADA MEDIA TANAM TANAH KAPUR - MEGA CHARISMA, ACIVRIDA Mega (Universitas Negeri Surabaya, 2012)
Soybean productivity should be increased because of the increasingly strong demand. One method is the large of plant area. Therefore calcareous soil can be used as an alternative grown medium, but the contrains in the calcareous soil should be overcome. On of alternative effort to overcome the deficiencies of nutrients in the calcareous soil is the addition of Trichoderma compost and vesicular arbuscular mycorrhizal (VAM). The purpose of this study was to determine the influence of the compost on the soybean grown on the calcareous soil. Experimental study was conducted using Randomized Completely Block Design (RCBD) by a factor of Trichoderma compost treatment (0 g, 15 g, 30 g and 45 g) with six replications. Measured parameters were the percentage of mycorrhizal infection, the percentage of active root nodules, plant height, root length, biomass of soybean. Data were analyzed using one-way ANAVA and continued to by the LSD if there were a significant different. The results showed that of compost consist Trichoderma and VAM affected significantly on the percentage of VAM infection, the percentage of active root nodules, plant height, root length, and biomass plants. The most optimal concentration of Trichoderma compost from all five parameters is 45 grams.